Contribution of the social and financial leadership education program to students and teachers - AVCI, SÜLEYMAN (My University, 2023)
The social and financial leadership training program started to be implemented in Turkey in 2015 with the training of trainers, and a wide-ranging application covering the whole of Turkey was carried out in the 2020–2021 academic year. The project is aimed to provide students with knowledge and attitudes within the scope of social and financial leadership, and teachers with the ability to apply student-centered teaching methods as well as knowledge and attitude in the subject area within the scope of professional development. For the project, an open announcement is made for all teachers in Turkey working in the 3rd and 4th grades of the primary school and the 6th and 7th grades of the secondary school. 320 teachers and 3786 students from 81 provinces who applied for the announcement were included in the project. In the project, teacher training is carried out through active learning methods and in line with professional development principles, in 12 sessions of 2 h, in groups of 30, by 21 mentors. On the other hand, student training, lasted for five months, with a theme each month, between November and March by teachers under the guidance of mentors. All stages of the project were carried out through online training. Pre-test and post-test data were collected through knowledge, attitude, and skill scales developed for teachers and students within the scope of the research. The findings obtained in the research reveal that the social and financial leadership training program is effective in gaining knowledge and attitudes in the subject area in students and teachers.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Hukuk; Eğitim; Social Sciences and Humanities; Sociology; Law; Education; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; SOSYAL BİLİMLER, İNTERDİSİPLİNER; HUKUK; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, INTERDISCIPLINARY; LAW; Sosyal Bilimler ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (çeşitli); Sosyal Bilimler (çeşitli); Genel Sosyal Bilimler; Social Sciences & Humanities; Arts and Humanities (miscellaneous); Social Sciences (miscellaneous); General Social Sciences; Financial literacy; Instructional design; Professional development of teachers; Social and financial leadership training; Student centered teaching; Teacher training